Alaska school characteristics and teacher retention, 2009-2015 - Kaden, Ute (Arctic Data Center, 2018)
High teacher turnover in rural Alaska is costly and prevents indigenous students from entering career pathways or college education. To provide equity and access to quality education, Arctic Alaska needs a consistent and culturally responsive teacher workforce that is integrated into the community life. The dataset examines school characteristics, reading/writing, and mathematics test scores. students enrollment, teacher attrition, and related demographics variables of 78 rural Alaska schools.